2015
DOI: 10.3109/09638288.2015.1061601
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an individual, multistep intervention on adherence to treatment in hemodialysis patients

Abstract: Adherence to treatment is one of the major problems in hemodialysis patients; however, comprehensive interventions are required in view of individual condition. Implications for Rehabilitation Adherence to treatment means that all patients' behaviors (diet, fluids and drugs intake) should be in line with the recommendations given by healthcare professionals. There is evidence on the association between adherence to treatment and decreased risk of hospitalization in dialysis patients. Individual structured prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
4
3
1
1
Order By: Relevance
“…This is consistent with the results of Rafiee Vardanjani et al (24) and Masror Roudsari et al (25). Rafiee Vardanjani et al (24) reported moderate dietary compliance, the chronic nature of the disease, economic problems, and the lack of patients' awareness as important factors affecting the quality of life. Hadi et al (26), indicated that drug compliance was lower among patients with hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results of Rafiee Vardanjani et al (24) and Masror Roudsari et al (25). Rafiee Vardanjani et al (24) reported moderate dietary compliance, the chronic nature of the disease, economic problems, and the lack of patients' awareness as important factors affecting the quality of life. Hadi et al (26), indicated that drug compliance was lower among patients with hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…Both increases were statistically significant. Our findings are parallel to the studies that aim to improve treatment adherence scores by using multidisciplinary education (Saunders et al, 2019), multidimensional education (Zhianfar et al, 2020), telephone counseling and follow-up (Salimi Ezzat et al, 2018), and multi-staged individual intervention (Vardanjani et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Studies aimed at improving treatment adherence with methods other than MI (e.g., education, consultation, selfmanagement and psychosocial intervention) mostly reported significant changes in patients' adherence to fluid restriction (Cukor et al, 2014;Griva et al, 2018;Howren et al, 2016;Moattari et al, 2012;Saunders et al, 2019;Vardanjani et al, 2016;Zhianfar et al, 2020). Some of these studies evaluated changes in biochemical parameters and reported changes in some of the parameters and no change in others (Griva et al, 2018;Moattari et al, 2012;Saunders et al, 2019;Vardanjani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai pendekatan intervensi yang diidentifikasi dalam penelitian ini yaitu intervensi pendidikan untuk meningkatkan pengetahuan (Alikari et al, 2019;Bakarman et al, 2019;Başer & Mollaoğlu, 2019;Mina et al, 2019;Rafiee Vardanjani et al, 2016;Youssef Sharaf, 2016;, self regulation model (Howren et al, 2016), dukungan psikososial dan social support programme (Griva et al, 2018;Mansouri et al, 2020;Tao et al, 2020), penerapan motivational technique (Crown et al, 2017), self-care and selfmanagement berdasarkan konstruksi teori perilaku kognitif (Mahjubian et al, 2018;Zhianfar, Nadrian, Jafarabadi, et al, 2020).…”
Section: Intervensi Psikoedukasi Sacara Langsungunclassified